Analisis Perbandingan Kinerja Keuangan Perbankan Syariah Di Indonesia Dan Malaysia Periode 2014 - Iriyanto, Guruh; , M. Sholahuddin, S.E., M.Si (2015)
This research was conducted to compare the financial performance of Islamic banking in Indonesia and Islamic banking in Malaysia. If reviewed in depth Indonesia has a Muslim population of nearly 90% of the total community, the economic outlook is so bright range from 6% -6.5%, and abundant natural resources that can be used as underlying Islamic finance industry. However, the ranking of Indonesian Islamic banking only able to occupy the world's seventh ranked much lower than Malaysia were able to occupy the second rank world. To evaluate the performance of the bank, this study using RGEC (Risk represented by the ratio of FDR (Financing to Deposit Ratio), assessment of Good Corporate Governance (GCG) or corporate governance, Earnings represented by ROA (Return on Assets), and Capital represented by the CAR (Capital Adequacy ratio). the scoring system uses a ratio that continued to test the difference by using Menn-Whitney test. The results showed that there were significant differences in both the ratio is the ratio FDR Indonesian islamic banking is far better than the islamic banking in Malaysia, will be directing that the utilization of funds for financing the Indonesian banking system is quite efficient but ROA shows that the profitability of the banking Malaysia much more well meaning business efficiency in addressing the risk profile is very effective. While the two other judgments, namely GCG and CAR, shows no difference.